1981
DOI: 10.1099/0022-1317-54-2-273
|View full text |Cite
|
Sign up to set email alerts
|

Assay of Defective-interfering Semliki Forest Virus by the Inhibition of Synthesis of Virus-specified RNAs

Abstract: SUMMARYWe describe a simple, rapid and reproducible assay for defective-interfering Semliki Forest virus (DI SFV) which is based on the inhibition of synthesis of virus-specified RNAs in SFV-infected cells. Using the assay, we have been able to show that DI virus is generated by a single passage in baby hamster kidney (BHK) cells in an inoculum which contained no detectable DI virus and we have calculated the u.v. target size of the interfering activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Barrett et al (1981) reported that interference by SF virus DI particles varies depending upon the cell line used for assay. Stark & Kennedy (1978) could not generate SF virus DI particles in HeLa cells, even after 200 serial passages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrett et al (1981) reported that interference by SF virus DI particles varies depending upon the cell line used for assay. Stark & Kennedy (1978) could not generate SF virus DI particles in HeLa cells, even after 200 serial passages.…”
Section: Discussionmentioning
confidence: 99%
“…Defective interfering (DI) particles are a class of virus deletion mutant generated during infection initiated at both high and low multiplicities (for reviews, see Perrault, 1981 ;Barrett et al, 1981). They have a number of common properties, which include the inability to propagate in the absence of homologous standard virus, and the ability to decrease the yield of standard virus and increase their proportion of the yield from cells coinfected with standard virus (Huang & Baltimore, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Since the standard virus genome represents about 6.3 ~o of the particle mass (Laine et al, 1973) and DI particles have smaller RNA species, this difference should be detected by estimates of particle density. However, the data are conflicting: Shenk & Stollar (1973) and have reported that DI virus particles are more dense than standard virus particles while others found no difference in their densities (Weiss & Schlesinger, 1973;Guild & Stollar, 1975;Logan, 1979 Detailed studies were made of a DI virus preparation which had been propagated for 13 undiluted passages (called DI SFV pl 3g) in BHK cells as described by Barrett et at. (1981).…”
mentioning
confidence: 99%
“…(1981). DI virus and standard virus (Barrett et al, 1981) were concentrated by centrifugation at 90 000 g for 3 h at 4 °C and resuspended in 50 mM-Tris-HC1, 100 mM-NaC1, 1 mM-EDTA, pH 7.4, but were not purified further. Virus was prepared for electron microscopy by placing I0 ~tl aliquots onto 2~ agarose in phosphate-buffered saline (PBS) in the wells of a microtitre plate.…”
mentioning
confidence: 99%
See 1 more Smart Citation